Evaluating the cooling potential of green open spaces in urban environments - Dwi Setyawan Ahmad; Suhardono Sapta; Indrawan Muhammad; Afzanaya Rarasti Khansa; Wijayanti Sovia (BIO Web of Conferences)
This study evaluated the cooling potential of Green Open Spaces (GOS) in Surakarta City, focusing on three parks: Sekartaji Park, Pucang Sawit Park, and Balaikambang Park. The aim was to measure the correlation between vegetation indices and land surface temperature (LST) to evaluate the influence of urban green spaces on the adjacent thermal environment. Using satellite imagery, various vegetation indices, including NDVI, SAVI, and EVI2, were calculated alongside LST assessments. The findings revealed that Balaikambang Park exhibited the most significant cooling impact, with a maximum cooling intensity of 2.55 at a buffer distance of 300 meters, while Pucang Sawit Park recorded a high of 2.14 at 400 meters. Sekartaji Park demonstrated a diminished cooling intensity, reaching a maximum of 1.31 before seeing a substantial decline at 500 meters. Correlation research indicated a substantial negative correlation between vegetation proportion and land surface temperature, especially in Pucang Sawit Park. The findings underscore the significance of vegetation in regulating urban temperatures and stress the necessity for efficient management of Green Open Spaces to optimize their cooling capacity.